Polyaniline-Coated Porous Vanadium Nitride Microrods for Enhanced Performance of a Lithium–Sulfur Battery - Jingjie Lv; Haibo Ren; Ziyan Cheng; Sang Woo Joo; Jiarui Huang (Molecules, 2023)
To solve the slow kinetics of polysulfide conversion reaction in Li-S battery, many transition metal nitrides were developed for sulfur hosts. Herein, novel polyaniline-coated porous vanadium nitride (VN) microrods were synthesized via a calcination, washing and polyaniline-coating process, which served as sulfur host for Li-S battery exhibited high electrochemical performance. The porous VN microrods with high specific surface area provided enough interspace to overcome the volume change of the cathode. The outer layer of polyaniline as a conductive shell enhanced the cathode conductivity, effectively blocked the shuttle effect of polysulfides, thus improving the cycling capacity of Li-S battery. The cathode exhibited an initial capacity of 1007 mAh g−1 at 0.5 A g−1, and the reversible capacity remained at 735 mAh g−1 over 150 cycles.